Literature Review: Factors Affecting the Use of 3-Month Injective Hormonal Contraceptions - Al Hakim, Annisa; Sunarti, Sunarti; Sulistyawati, Sulistyawati (Universitas Ibn Khaldun Bogor, 2024)
According to WHO (World Health Organization), family planning is an action that helps married couples to avoid unwanted births, regulate pregnancy intervals, control the timing of pregnancy in relation to the age of husband and wife and determine the number of children in the family. One factor that increases population is fertility or births. This research is a literature review research using national journals and international journals in English through searches in two databases including Google Scholar and Pubmed. The inclusion criteria used in this study were journals that examined factors influencing the use of 3-month injectable hormonal contraception and had a publication year in the last 10 years. The results of the study show that there is a significant relationship between factors that influence 3-month injectable hormonal contraception. Based on the articles that have been collected, the research results show that age and level of education are the main factors influencing the use of 3-month injectable birth control contraception. Based on the results of the discussion above, it can be concluded that the factors influencing the use of 3-month injectable contraception are influenced by 1). Age Factor, 2). Weight gain factors 3) Education factors.